Effect of ammonia energy fractions on combustion stability and engine characteristics of gaseous (ammonia/methane) fuelled spark ignition engine. (12th January 2023) - Kurien, Caneon; Varma, Penmatsa Sandeep; Mittal, Mayank
Abstract: Non-carbon nature and higher hydrogen energy density of ammonia have gained a lot of interest as an energy asset and green fuel. In this work, the effects of ammonia fuel share and engine operating load on the combustion stability and engine characteristics (combustion and performance) of gaseous (NH3 /CH4 ) fuelled SI engine have been reported. The lower heating value and flame propagation speed of fuel mixture reduce with the increase in ammonia share (0–60% at 8 Nm engine load) and thus results in detrimental engine performance and higher cycle-to-cycle combustion variations (1.36%–14.9% COV of IMEP). A rise in operating load from 8 Nm to 16 Nm increases the flame propagation speed of the fuel mixture (60% ammonia share) and improves engine performance and combustion stability (14.9%–4.3% COV of IMEP). The results of this study indicate that the substitution of methane with ammonia could be maximized at higher engine operating loads to get the benefit of clean fuel utilization. Graphical abstract: Image 1 Highlights: Green ammonia as a hydrogen energy carrier and potential fuel for IC engines. Study on the effect of ammonia addition in methane fuelled Spark Ignition engine. Increasing share of NH3 in fuel mixture at lower loads reduced combustion stability. Enhancement of operating limits at higher engine loads in methane fuelled engines by NH3 addition.